The ability to do otherwise and the new dispositionalism. Issue 9 (21st October 2022) - Jaster, Romy
ABSTRACT: According to the new dispositionalist's response to the Frankfurt cases, Jones can do otherwise. Black merely masks (or finks) that ability, but does not deprive Jones of it. This suggestion stands in the tradition of a line of thought according to which an informed view of the truth conditions of ability attributions allows for a compatibilist stance. The promise is that once we understand how abilities work, it turns out that the ability to do otherwise is compatible with determinism, or with Black standing ready to intervene, or indeed both, as the new dispositionalists hold. I argue that this is mistaken. Understanding how abilities work gives us no reason to think that the ability to do otherwise relevant for free will is compatible with either Black's presence or determinism.